Clinico-epidemiological profile of trauma victims in a tertiary care hospital in rural setting of Central Uttar Pradesh - Singh, Naresh Pal; Singh, Ramit Chandra; Singh, Vikas; Jain, Pankaj K; Gupta, Poonam; Singh, Anamika (Indian Journal of Community Health, 2017)
Background: In the present scenario of unprecedented population growth and development in India, we are also facing tremendous increase in cases of trauma victims and this burden is not only in economic terms, but also has significant physical, mental and social impacts. Aim and objectives: To determine the clinic-epidemiological profile and treatment outcome of trauma victims in a tertiary care hospital in rural setting. Material and Methods: A cross-sectional hospital based study was carried out on 700 trauma victims reporting the hospital at Uttar Pradesh University of Medical Sciences in Etawah district of Uttar Pradesh for a duration of one and half year i.e. from January, 2015 to June, 2016. A clinico-epidemiological profile of the study subjects including specific details like mechanism and type of injuries, interval of presentation of trauma victims to the hospital and treatment outcome of the injury was recorded. The data was analysed using spss software 21st version. Results: Study revealed that nearly two-thirds (63.43%) of the studied trauma victims were in the 10-40 years of age-group with three-fourth of them being males (75.57%). Road traffic accident was the most common mechanism of injury (68.86%). Majority (88.0%) of trauma victims needed admission for management of injuries. Conclusion: Road Traffic Accident (RTA) is the major form of trauma received by the people and that too in majority by the youths hence proper behaviour change communication and health education regarding safety measures to prevent trauma should be provided to the youths.